2019
DOI: 10.1093/biosci/biy152
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Ecological Responses to Dam Removal: If You Remove It, What's to Come?

Abstract: One of the desired outcomes of dam decommissioning and removal is the recovery of aquatic and riparian ecosystems. To investigate this common objective, we synthesized information from empirical studies and ecological theory into conceptual models that depict key physical and biological links driving ecological responses to removing dams. We define models for three distinct spatial domains: upstream of the former reservoir, within the reservoir, and downstream of the removed dam. Emerging from these models are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 88 publications
(140 reference statements)
3
100
0
1
Order By: Relevance
“…(3) are influenced by many factors including hillslope-channel coupling, physical linkages among channel reaches, and hydrological regimes; (4) can follow many trajectories; (5) are intricately intertwined with ecological recovery; and (6) that systems may not return to predisturbance states (e.g., Bellmore et al, 2019;Cluer & Thorne, 2014;East et al, 2018;Foley et al, 2017;Gellis et al, 2017;Gran et al, 2011Gran et al, , 2013James, 1991;James & Lecce, 2013;Kasai, 2006;Kasai et al, 2004;Major et al, 2018;Moody & Meade, 2014, 2018Pierson & Major, 2014;Schumm, 2005;Swanson & Major, 2005). But we can further exploit records of physical responses to profound fluvial disturbances to gain richer geomorphic insights.…”
Section: 1029/2018jf004843mentioning
confidence: 99%
See 1 more Smart Citation
“…(3) are influenced by many factors including hillslope-channel coupling, physical linkages among channel reaches, and hydrological regimes; (4) can follow many trajectories; (5) are intricately intertwined with ecological recovery; and (6) that systems may not return to predisturbance states (e.g., Bellmore et al, 2019;Cluer & Thorne, 2014;East et al, 2018;Foley et al, 2017;Gellis et al, 2017;Gran et al, 2011Gran et al, , 2013James, 1991;James & Lecce, 2013;Kasai, 2006;Kasai et al, 2004;Major et al, 2018;Moody & Meade, 2014, 2018Pierson & Major, 2014;Schumm, 2005;Swanson & Major, 2005). But we can further exploit records of physical responses to profound fluvial disturbances to gain richer geomorphic insights.…”
Section: 1029/2018jf004843mentioning
confidence: 99%
“…We have learned much by analyzing fluvial responses to past events. Studies have shown that geomorphic responses to fluvial disturbances (1) relax over varying timescales but can persist for years to decades, even centuries; (2) can be both acute and gradual; (3) are influenced by many factors including hillslope‐channel coupling, physical linkages among channel reaches, and hydrological regimes; (4) can follow many trajectories; (5) are intricately intertwined with ecological recovery; and (6) that systems may not return to predisturbance states (e.g., Bellmore et al, ; Cluer & Thorne, ; East et al, ; Foley et al, ; Gellis et al, ; Gran et al, , ; James, ; James & Lecce, ; Kasai, ; Kasai et al, ; Major et al, ; Moody & Meade, , ; Pierson & Major, ; Schumm, ; Swanson & Major, ). But we can further exploit records of physical responses to profound fluvial disturbances to gain richer geomorphic insights.…”
Section: Introductionmentioning
confidence: 99%
“…), giving a better understanding of how ecosystems respond (Bellmore et al. ). Of the 565 publications mentioning the topic “dam removal” since 1994 (Figure B), 64 publications (articles and reviews) have been published in fisheries‐focused journals with 40 of those published in AFS journals.…”
mentioning
confidence: 99%
“…An update is also necessary because the knowledge from dam removal studies has increased over the last 15 years (Bellmore et al 2017), giving a better understanding of how ecosystems respond (Bellmore et al 2019). Of the 565 publications mentioning the topic "dam removal" since 1994 ( Figure 1B), 64 publications (articles and reviews) have been published in fisheries-focused journals with 40 of those published in AFS journals.…”
mentioning
confidence: 99%
“…Changes in life history diversity of fishes upstream of former dams, such as re‐expression of migratory forms or changes in length at age, are not well documented (Bellmore et al. ). This historic project provides opportunities to assess the life history responses of migratory Bull Trout and the recovery of this threatened species.…”
mentioning
confidence: 99%